O agir linguageiro de professores de língua inglesa frente ao PNLD como politica linguística - Nessralla, Marília (2017)
This dissertation aims to analyze the impact of the English language textbooks of PNLD 2012 for High School, considering this program as language policy (ROJO, 2013) for continuing education (NICOLAIDES, TÍLIO, 2013). It is a diagnostic, qualitative, interpretative, ethnographic research. The following methodological procedures were used: documentary analysis, interview with participants in the research, field notes of classes observation, and questionnaires to identify the profile of the participants. The analysis of the context of production (BRONCKART, 20012) of the English Language textbooks of PNLD 2012 showed that they were produced observing the provisions of the PCNEM (BRASIL, 2000) and PCN + Ensino Médio (2002), which indicate that the teaching-assessment-learning process is developed by themes, emphasizing reading and relating it to the development of critical literacy, as prescribed in OCEM (BRASIL, 2006). The studies revealed that the production of textbooks in the country is mainly based on the Grammar and Translation Method, which includes language as a product, disregarding the socio-historical and cultural context and the Reading Method. (CASTRO, 1988; LEFFA, 1988; SILVA, 1988; RICHARDS; RODGERS, 2008 PAIVA, 2012, 2014). The analysis of the textbooks used by the participants of the research showed, therefore, gaps in the teaching of pronunciation and vocabulary. Several theoretical-methodological conceptions are registered in the textbooks, with emphasis on the Grammar and Translation Method, Reading Method, with some activities of the Communicative Approach. Regarding the formation of citizenship which is the purpose of the insertion of modern foreign languages into basic education, the teaching of the English language aimed at reading bumps against the possibility of students to participate in government exchange programs, which require oral and production skills from the applicants. In this sense, there is no conception of systemic education established in the Education Development Plan. (BRASIL, 2008). The analysis of the teachers' representations about the process of choosing, using and evaluating the textoobks evidenced different perspectives according to the educational context. In the state institutions, emphasis was placed on teaching reading and preparation for large-scale state assessments and the National High School Examination (ENEM), with little development of critical literacy. In the federal institution, in addition to reading, the teacher aims to develop oral comprehension and oral production. It is concluded that the English Language textbooks of PNLD 2012 can provide the development of critical literacy, although they have little potential for the development of communicative competence. This aspect compromises the objective of forming citizens for the full exercise of their rights and duties, according to curricular guidelines for this level of education. In this context, teachers act according to their representations about the teaching-assessment-learning process of the English Language in High School, within their working conditions and educational background.